DEPICTION OF SOCIAL CLASS IN BONG JOON-HO'S SNOWPIERCER (2013) - Gading, Mayang Puspa (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
This study explores the portrayal of social classes in the film Snowpiercer (2013) through the lenses of Karl Marx's and Guy Standing’s theories. Social class, defined as groupings of individuals based on shared wealth and status within a societal hierarchy, serves as the central focus. The analysis draws on dialogue and visual imagery from the film to explore how these classes are depicted and their interactions examined. The bourgeoisie, represented by the elite, salariat, and proficians, wield significant power and privilege within the train's stratified society. In contrast, the proletariat—comprising the working class, precariat, unemployed, and detached—is marginalized, enduring harsh conditions and limited access to resources. This analysis underscores the film's exploration of social class, highlighting themes of inequality and the human condition in a dystopian setting. Future research could further enrich understanding by exploring alternative theoretical frameworks and comparative analyses across different media and genres. Keywords: social class, contributing factors, inequality, wealth, resources.